A new species of the pontoniine shrimp genus Hamopontonia Bruce, 1970 associated with caryophyllid coral Euphyllia glabrescens (Chamisso & Eysenhardt, 1821) in Nhatrang Bay, Vietnam - Marin, Ivan (Zootaxa, 2014)
Hamopontonia nhatrangensis sp. nov. (Crustacea, Decapoda, Palaemonidae, Pontoniinae) is described from Nhatrang Bay, Vietnam, in association with caryophyllid coral Euphyllia glabrescens (Chamisso & Eysenhardt, 1821) (Hexacorallia, Scleractinia, Caryophyllidae). The new species clearly differs from congeners by morphological features, distinctive coloration and ecologically. Renewed differential key to all known species of the genus Hamopontonia Bruce, 1970 is provided.